Reproductive patterns in Leptodactylus fuscus: how crucial is rainfall in breeding periods? (2020)
Amphibians show a great diversity of species and reproductive modes. Categories of reproductive modes among anurans (frogs and toads) are based mainly on how and where eggs are deposited. These differences are related to the interaction between the environmental conditions where anurans live and their mating systems. Despite their dependency on water for their survival and reproduction, frogs of the family Leptodactylidae have evolved traits such as the foam nest that allows them to survive dry periods during the breeding season. Within the Leptodactylus fuscus Species Group, the species L. fuscus has a vast distributional range in South America, despite the wide geographic variation in climatic conditions. In this study, I evaluated if variables such as rainfall and geographic variation affect the reproductive seasonality of L. fuscus. First, I tested for sexual dimorphism in this species. This was done by collecting data from natural history museum specimens of L. fuscus captured in 4 regions of Colombia. The morphological variables included snout-vent length (SVL), sex (determined by inspecting gonads), follicle development in females, month, year and location of capture, and vocal sac coloration. I compared these variables to the amount of precipitation in the date and place of the capture. My results showed that females have a longer average SVL than males and that only males have black vocal sac coloration, which is acquired with sexual maturity. My analyses suggest a greater number of juveniles approximately 2 months after the rainfall season starts. Throughout most of the year, regardless of the season in which the specimen was captured, females with fully developed follicles were observed. I used generalized additive models (GAM) to understand which variables were most strongly related to the reproductive status of females and males. Rainfall from the month before and after capture were the strongest predictors of SVL and follicle development.